Direct Adventitious Shoot Regeneration from Triploid Watermelon Cotyledons - Ha, Ha Thi Thuy; Huyen, Nguyen Thi Thanh; Diep, Le Hong (VNU Journal of Science: Natural Sciences and Technology, 2016)
Abstract: An in vitro regeneration system was established for cotyledon explants of triploid watermelon ( Citrullus lanatus Thumb.). Full strength MS medium supplemented with 0.2 mg.L -1 IAA in combination with different concentrations of BAP was employed for investigating adventitious shoot formation. Medium containing 1.5 mg.L -1 BAP and 0.2 mg.L -1 IAA was suitable for direct shoot induction from cotyledon explants. Adventitious shoots were elongated for 3 weeks on medium containing 0.5 mg.L -1 GA3 before transferring into rooting medium. Frequency of root induction achieved approximately 88% with an average of 4.3 root per shoot on half strength MS medium supplemented with 0.5 mg.L -1 IBA. Rooted shoots were successfully acclimatized in potted soil mixture with survival rate of 82.6%. Keywords: Triploid, Citrullus lanatus , regeneration.